A production inventory model for vendor–buyer coordination with quantity discount, backordering and rework for fixed life time products. (17th August 2016) - Muniappan, P.; Uthayakumar, R.; Ganesh, S.
Abstract : This study develops perishable items production inventory models with backordering and rework process. In the absence of coordination, shortages are allowed for the buyer and damaged products are returned to the vendor. The vendor himself makes arrangement for screening or disposal of the damaged products. During coordination strategy, shortages are not allowed, the quantity discount is provided to the buyer and the damaged products are not returned to the vendor. The buyer himself makes the arrangement for screening or disposal of the damaged products. In both cases, optimum multiples of orders and optimum order quantity are determined by vendor and buyer, which will minimize the total inventory cost. It proves that the coordination strategy can achieve system optimization. A numerical example is given to illustrate the solution procedure for the model. Finally, based on the example, we have conducted a sensitivity analysis of the model.